The effect of topical olive oil on prevention of bedsore in intensive care units patients - Madadi, Zahra Abbas Ali; Zeighami, Reza; Azimian, Jalil; Javadi, Amir (International Journal of Research in Medical Sciences, 2017)
Background: Bedsores are injuries to skin and underlying tissues caused by prolonged pressure. Although, some methods like frequently changing position and using particular tools are used for preventing and caring of pressure ulcers, their prevention would still be as a vital urgency. Olive oil is an herbal product with potential preventive effects to prevent bedsores because of its numerous medical properties. The major aim of this study was to determine whether topical olive oil can prevent the risk of developing bedsores in I.C.U. patients. Methods: This clinical trial was accomplished in 2014 with 60 patients who were selected by simple random sampling method into intervention and control groups. During three weeks, the control group had received routine skin care, while the intervention group had received topical Olive oil in addition to the routine care. Statistical analysis, including Chi-square, T-test and Fisher’s tests, were performed with SPSS version 20 software. Results: The intervention group had contained 19 male and 11 female, with an average age of 60.46 ± 18.06 and the control group had contained 20 male, 10 female, with an average age of 50.96 ± 21.38. Five patients (16%) who received routine care plus topical olive oil had developed bedsore after an average of 18.73 ± 5.36 days and twelve patients (40%) who received routine care only had developed bedsore after an average of 15.46 ± 7.40 days. The risks of developing bedsores between two groups were statistically significant (P=0.03). Conclusions: Our study has revealed potential effects of topical olive oil to prevent bedsores in I.C.U. patients.